A Bovine Cell Line That Can Be Infected by Natural Sheep Scrapie Prions - Oelschlegel, Anja M. (PLoS One, 2015)
Cell culture systems represent a crucial part in basic prion research; yet, cell lines that are susceptible to prions, especially to field isolated prions that were not adapted to rodents, are very rare. The purpose of this study was to identify and characterize a cell line that was susceptible to ruminant-derived prions and to establish a stable prion infection within it. Based on species and tissue of origin as well as PrP expression rate, we pre-selected a total of 33 cell lines that were then challenged with natural and with mouse propagated BSE or scrapie inocula. Here, we report the successful infection of a non-transgenic bovine cell line, a sub-line of the bovine kidney cell line MDBK, with natural sheep scrapie prions. This cell line retained the scrapie infection for more than 200 passages. Selective cloning resulted in cell populations with increased accumulation of PrP(res), although this treatment was not mandatory for retaining the infection. The infection remained stable, even under suboptimal culture conditions. The resulting infectivity of the cells was confirmed by mouse bioassay (Tgbov mice, Tgshp mice). We believe that PES cells used together with other prion permissive cell lines will prove a valuable tool for ongoing efforts to understand and defeat prions and prion diseases.